AFRICA’S SEARCH FOR PEACE AND STABILITY: DEFENSE DIPLOMACY AND CONFLICT RESOLUTION IN THE DEMOCRATIC REPUBLIC OF CONGO (DRC) - Gugulethu Linda Nyathi; Helda Risman (The Republic of Indonesia Defense University, 2020)
Several conflict interventions have been taken place in the DRC, including political and diplomatic efforts. In 1998, the South African Development Cooperation (SADC) intervened through a combination of military and mediation activities. There was a military intervention from three SADC countries - Angola, Namibia, and Zimbabwe, under the auspices of the SADC Allied Forces. Recovery from the conflict that occurred from 2003 up to 2019 has not been smooth. The main cause of the second war was politics. President Laurent Kabila was seeking to expel Rwanda from the government. Rwandan troops supporting the Tutsi invaded and social conflict with ethnic connotations increased. The conflict continued until a transitional government was created to share power among all vice presidents. At that time, it was perceived that a military outcome would not produce the lasting peace required for the reconstruction of the DRC.